ANALISIS PANEL ATAS PENGARUH EKONOMI DAN SOSIAL MASYARAKAT TERHADAP KEMANDIRIAN FISKAL PEMERINTAH KABUPATEN/KOTA DI SULAWESI UTARA - Karamoy, Herman; Poputra, Agus Tony (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
This paper analyzes the impact of economic and social variables on fiscal independence of district government in Province of North Sulawesi.Â  Scope of research includes all districts inÂ  2009-2012. To analyze secondary data, we utilize the Pooled EGLS (Cross-section random effects) method. This research not only use secondary data, but also primary data. The primary data are used to get deep picture about factors that lower fiscal dependence of districts in North Sulawesi. Those data are collected by interview to parties related to generate own resource revenues and by focus discussion group with academicians. This research finds that economic development and population in districts of North Sulawesi do not affect on fiscal independence. Otherwise, only variable human development index has significantly positive effect on fiscal independence. These findings are supported by primary data which show that: (1) most activities of dominant economic factor of those districts, except Manado and Bitung, namely agriculture, are not tax or surcharge objects; (2) types of local government tax have small tax base for districts and varies between dictricts that have big cities and small cities; (3) low of human resource capacity and creativity to generate own source revenues effectively and efficiently; and (4) low of taxpayers compliance.